Peningkatan Hasil Belajar Ipa Melalui Model Pembelajaran Kooperatif Tipe Numbered Heads Together Pada Peserta Didik Kelas IV SDI Ngalupolo - Adi Neneng Abdullah (Program Studi Pendidikan Ekonomi, Universitas Flores, 2021)
The type of research used is classroom action research (CAR). This research is used to identify and clearly describe the activities related to the contextual approach by using the Numbered Heads Together model. The research subjects in this study were all students of class IV SDI Ngalupolo totaling 28 people. The research was carried out in the Class Action Research (CAR) stage of the Kemmis and Mc Taggart design which included the planning stage (Plan), the implementation stage (Act), the observation stage and the reflection stage. The data collection methods used in this study were tests, observations, interviews, and documentation. The results of this study indicate an increase in student learning outcomes, this is evidenced by the results obtained in cycle I and cycle II where the percentage of completeness in cycle I is 55.71%, and increases in cycle II to 85.71% and is included in the level of success in the very good category. . By looking at the results of the analysis of the research data, it was concluded that using the NHT type of cooperative learning model can improve the learning outcomes of fourth grade students of SDI Ngalupolo science subjects with natural resource materials.